Implementasi User-Centered Design pada Perancangan Prototype Aplikasi Pendampingan Pasien Pasca Rehabilitasi Gangguan Jiwa - Astria Hijriani (Jurnal SITECH : Sistem Informasi dan Teknologi, 2026)
Post-rehabilitation mental health patients require continuous assistance and monitoring to prevent relapses and improve their quality of life. However, limited communication between caregivers and healthcare professionals often hinders effective patient monitoring. This study aims to develop the JiwaMuKu application prototype as a digital assistance platform for post-rehabilitation mental health patients using the User-Centered Design (UCD) approach. The research stages consisted of identifying the context of use, eliciting user requirements through interviews with the Indonesian Mental Health Nurses Association (Ikatan Perawat Kesehatan Jiwa Indonesia – IPKJI), designing the prototype, and evaluating usability using the System Usability Scale (SUS). The identified requirements resulted in several key features, including symptom assessment, capability assessment, self-care guidance, reminders, patient monitoring, and communication between caregivers and healthcare professionals. Usability evaluation was conducted with 30 respondents and produced an average SUS score of 75.33. The result indicates that the developed prototype falls within the acceptable category and demonstrates good usability. Furthermore, system validation with IPKJI confirmed that the proposed features adequately addressed user requirements.